Fruit quality, antioxidant enzymes activity and yield of six cultivars of grapefruit (Citrus paradisi) grown under subtropical conditions - DUBEY, A K; SRIVASTAV, MANISH; KAUR, CHARANJEET (The Indian Journal of Agricultural Sciences, 2026)
Experiment was conducted on six cultivars of grapefruit (Citrus paradisi Macf.) namely, Imperial, Duncan, Foster, Marsh SL, Star Ruby and Redblush during 2009-2011. Plants of these cultivars were spaced at 4 m × 4 m apart. Fruit yield was found to be the highest (31.48 kg/tree) in Imperial followed by Foster (23.43 kg/tree). However, heaviest fruit (414.01 g) was recorded in Foster and the lowest fruit weight (282.89 g) was in Redblush. Duncan and Marsh SL had the highest juice recovery (50.00%) which was not differed significantly with Redblush (46.91%). The lowest juice recovery was found in Foster and Imperial. Imperial had thickest peel (6.99 mm) and peelthickness was least in Foster (5.30 mm). Whereas, seeds/fruit was recorded the highest in Foster and Imperial (> 44 seeds/fruit). Other cultivars like, Marsh SL, Star Ruby and Redblush had less than 5 seeds/fruit and seems to be seedless. Mean TSS was recorded maximum in Duncan (9.56%) which was at par with Marsh SL (9.53%) and Redblush (9.50%). The minmum TSS was found in Star Ruby (8.82%) which did not differ significantly with Foster. Significantly lower acidity was recorded in Marsh SL (0.81%), Imperial (0.85%) and Foster (0.94%). While maximum acidity was found in Duncan (1.09%). The higher ascorbic acid content (56.53 mg/100 ml juice) was estimated in Marsh SL followed by Foster (49.61 mg/100 ml juice). Whereas, maximum AOX activity (5.56 µ mol Trolox eq/g ) was recorded in Imperial followed by Marsh SL (5.08 µ mol Trolox eq/ g) and Redblush (4.53 µ mol Trolox eq/g). The most promising grapefruit cultivars, based on yield and quality, were Marsh SL, Redblush and Imperial.